Acquired Alterity Migration, Identity, and Literary Nationalism - Mack, Edward (University of California Press, 2022)
This is the first book-length study in English of the Japanese-language literary activities of early Japanese migrants to Brazil. It provides a detailed history of Japanese-language bookstores, serialized newspaper fiction, original creative works, and critical apparatuses that existed in Brazil prior to World War II. This case study of the reading and writing of one diasporic population challenges the dominant mode of literary study, in which texts are often explicitly or implicitly understood through a framework of ethno-nationalism. Self-representations by writers in the diaspora reveal flaws in this prevailing framework through what Edward Mack calls "acquired alterity," in which expectations about the stability of ethnic identity are subverted in surprising ways. Acquired Alterity encourages a reconsideration of the ramifications (and motivations) of cultural analyses of texts and the constructions of peoplehood that are often the true objects of literary knowledge production. "Acquired Alterity is a trailblazing work on an extremely promising new topic of research in Japanese literary studies. Over the last decade we have seen a turn to writings produced in other regions that saw mass immigration from Japan. Grounded in exhaustive research, this book is the first to introduce this enormously interesting and important body of writings to English-language readers." MICHAEL BOURDAGHS, Robert S. Ingersoll Professor of East Asian Languages and Civilizations, University of Chicago